Depression among cancer survivors – An untold story - Jacson, Janice (Indian Journal of Pharmacy & Drug Studies, 2023)
Mental health is an important area in the treatment of patients. Cancer not only burdens the individual during the treatment phase but also during the survivorship period. Multi-morbidities, being female, pre-existing psychological illness are few among risk factors that intensify the course of depression among cancer survivors. Depression can seep in through various means from the effects of treatment to accepting the reality of survivorship and it may vary depending on the type of cancer. Screening and assessing for depression, patient self management strategies, internet based mindfulness therapy and psychoeducational interventions are few among the possible ways to tackle the threat of depression in cancer survivors. This review summarizes the causes of depression, depression among various cancer types (thyroid, prostate, breast and rectal/ colorectal cancer) and applications of evidence to practice to overcome depression in cancer survivors.